Review of quality of life studies in women with alopecia - D.S. Davis, MD, MS; V.D. Callender, MD (Wolters Kluwer, 2018)
Alopecia is a dermatologic condition that affects the pilosebaceous unit in both men and women. In addition to a thorough medical history and physical examination, a host of diagnostic tools may be warranted to differentiate nonscarring and scarring alopecias. Female pattern hair loss represents the most common form of hair loss experienced by up to 40% of women by a certain age. Although alopecia is a benign disorder, even the most negligible amount of hair loss can be devastating to a patient's self-esteem, self-image, and overall quality of life. We present this comprehensive review of quality of life studies in women with alopecia to describe the multitude of feelings and emotions associated with the disorder and remind dermatologists of the psychological impact it can have on women.